Upper Limb Muscles Activity during Punches in Virtual Reality Exergame on Standing and Sitting Position - Putra, Bayu Aji Mayogya; Masduchi, Reni Hendrarati; Tinduh, Damayanti; Pawana, I Putu Alit (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Physical activity (PA) provides various health benefits. Unfortunately, individuals with disabilities may experience health problems and greater obstacles to PA participation. Boxing exergame (EXG) based on virtual reality (VR) can be an alternative option to increase physical activity level because it is fun, relatively affordable and accessible. Punching in boxing requires complex movements, wherein the lower limbs are contributor for effective punches. An understanding of muscles activity is important to uncover the potential benefits of VR EXG.Aim: To evaluate the differences in upper limb muscles activity of the dominant side in standing compared to sitting position during punches.Material and methods: This was a cross-sectional study involving 15 healthy adult men. Surface electromyography examinations was performed on four upper limb muscles of the dominant side (upper trapezius, anterior deltoid, biceps, triceps) when delivering straight, hook and uppercut punches while playing VR EXG